Considerations About Criminal Actors in Colombia, as Mutations of the Internal Conflict, from the Economic Perspective and the History of International Relations (2006-2018) [Considérations Sur Les Acteurs Pénaux de la Colombie, Comme Mutations Du Conflit Interne, Du Point de Vue Économique Et de L Histoire Des Relations Internationales (2006-2018)] [Consideraçõessobreosatorespenaldacolômbia,Comomutaçõesdoconflito Interno, Da Perspectiva Econômica E Da História Das Relações Internacionais (2006-2018)] [Consideraciones Acerca de Los Actores Criminales de Colombia, Como Mutaciones del Conflicto Interno, Desde la Perspectiva Económica y de la Historia de Las Relaciones Internacionales (2006-2018)] - Garcia-Perez, P (Sello editorial Universidad del Atlantico, 2021)
This study analyses the armed actors in Colombia s post-conflict from the partial demobilization of the United Self-Defenses Forces of Colombia (AUC in Spanish) in 2006 until the peace agreements signing with the Revolutionary Armed-Forces of Colombia-People s Army (FARC-EP). It aims at establishing the insurgent and counterinsurgent armed actors transformation into transnational criminal groups promoting criminal capitalism, taking advantage of institutional gaps and the absence of modern economic actors, thus impacting economic growth and potential development in the country s departments where they are concentrated. This paper works towards an initial framework to study the impact of institutional gaps, illegal economies and the presence of armed actors on economic growth in the Colombian departments most affected by violence. © 2021 Sello editorial Universidad del Atlantico. All rights reserved.